Análisis de la contribución de la educación financiera en el nivel de vida de los millennials: en las cuatro principales ciudades de Colombia (2020)
This degree work provides a detailed explanation of the importance of Financial Education in the Standard of Living of the Millennials population, based on an analysis in the four main cities of Colombia. It begins by examining the weight of Financial Education that covers the country and the Standard of Living that Millennials have today. This was done based on the results of surveys that were carried out on Millennials in Bogotá, Medellín, Cali and Barranquilla in order to have current first-rate support as each of the indicators has evolved and give the same answer to the hypothesis proposed.